(untitled) (CR. Conservación y Restauración, 2025)
This text is an overview of the activities carried out by the Departamento Protección del Patrimonio Cultural (Cultural Heritage Protection Department), a specialized federal unit of the Argentine Republic, which is responsible for the prevention and fight against illicit trafficking of cultural property. Over the years, this Office has successfully enhanced the training of its members in operating procedures and specific content related to this field. Also, various courses have been offered at different educational institutions, and numerous improved tools have been developed for our daily work. These advancements have helped this Office achieve a professional level that stands out both nationally and internationally. The area of investigations related to crimes affecting cultural property has shown an outstanding performance, with a clear objective and highly satisfactory results. In this text, we will briefly share some of the accomplishments of the Department over the past 20 years. During this time, we have successfully recovered 30 200 cultural items, which proves the exceptional performance of this Office.